What is in a greeting? The social meaning of greetings in Sweden-Swedish and Finland-Swedish service encounters - Nilsson, Jenny; Norrby, Catrin; Bohman, Love; Skogmyr Marian, Klara; Wide, Camilla; Lindström, Jan (My University, 2020)
This study investigates the use of greetings in Sweden-Swedish and Finland-Swedish service encounters and the social meaning of different greeting forms. Situated within the framework of variational pragmatics, the study explores Swedish as a pluricentric language and investigates with interactional and statistical analyses to what extent the variable nation affect variation in greeting forms. While nation indeed is an important factor, the study also illustrates how social variables such as age, gender and participant roles as well as situational variables such as medium, region and venue impact the greeting choices participants make. Further, by applying an interactional analytical perspective the study contributes to the methodological development of variational pragmatics. This analysis shows how the sequential position of a greeting plays a part in the choice of greetings, and demonstrates that pragmatic variation emerges in interaction. The article suggests that greetings can be a resource for indexing the degree of social distance between interlocutors, and thereby manifest recurring cultural patterns.